Validation of a microdose probe drug cocktail for clinical drug interaction assessments for drug transporters and CYP3A. Issue 4 (10th December 2016) - Prueksaritanont, T; Tatosian, DA; Chu, X; Railkar, R; Evers, R; Chavez‐Eng, C; Lutz, R; Zeng, W; Yabut, J; Chan, GH; Cai, X; Latham, AH; et al.
Abstract : A microdose cocktail containing midazolam, dabigatran etexilate, pitavastatin, rosuvastatin, and atorvastatin has been established to allow simultaneous assessment of a perpetrator impact on the most common drug metabolizing enzyme, cytochrome P450 (CYP)3A, and the major transporters organic anion‐transporting polypeptides (OATP)1B, breast cancer resistance protein (BCRP), and MDR1 P‐glycoprotein (P‐gp). The clinical utility of these microdose cocktail probe substrates was qualified by conducting clinical drug interaction studies with three inhibitors with different in vitro inhibitory profiles (rifampin, itraconazole, and clarithromycin). Generally, the pharmacokinetic profiles of the probe substrates, in the absence and presence of the inhibitors, were comparable to their reported corresponding pharmacological doses, and/or in agreement with theoretical expectations. The exception was dabigatran, which resulted in an approximately twofold higher magnitude for microdose compared to conventional dosing, and, thus, can be used to flag a worst‐case scenario for P‐gp. Broader application of the microdose cocktail will facilitate a more comprehensive understanding of the roles of drug transporters in drug disposition and drug interactions.